Reshaping digitalization: towards in-war ukrainian architecture [Articol] - Kiriiak, Oksana (CEP USM, 2024)
The main factor influencing world politics in the late twentieth and early twenty-first centuries is digitalization. Without considering its essence, causes, main forms and possible consequences for the world system, the analysis of modern world politics and security policy will be at least incomplete. The new quality of digitalization – globalization – consists not only in the fact that the level of interdependence and mutual vulnerability of states is increasing. In fact, the internal sovereignty of states is weakening in a growing range of political directions. Globalization limits the field of activity of the governments of individual countries in terms of the possibility of the sovereign formation of their societies, the isolated solution of problems affecting the national territory.